Peran Lembaga Amil Zakat dalam Meningkatkan Kesejahteraan Keluarga Janda Miskin Melalui Program Kampung Mandiri di Laznas Yatim Mandiri Kudus - Firda Ramadhanti; H. Fuad Riyadi (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2020)
The purpose of this research is to analyze the role of the Amil Zakat Institution (LAZ) in the economic sector to improve the welfare of poor widowed families, namely through the economic empowerment program of the Kampung Mandiri National Amil Zakat Institute (LAZNAS) Yatim Mandiri, Kudus Branch located in Cangkring B Village, Karanganyar District, Regency. Demak. The results showed that the LAZNAS Yatim Mandiri Kudus Branch program in the formation of the Kampung Mandiri program, namely first, planning the formation of the Kampung Mandiri program in Cangkring B Village Karanganyar Demak to the implementation of the program, with the business being managed is fried onions with the branding